Causal factors influencing job satisfaction for universities teachers in Hubei Province - Zhu, Jie; Boonphadung, Suttipong; Siththada, Thada (Edelweiss Applied Science and Technology, 2025)
Job satisfaction plays a pivotal role in developing higher education systems. It is crucial for enhancing teacher performance, student achievement, and educational quality. This research aims to study the causal relationships and mediating effects among these variables and propose guidelines for improving job satisfaction among university teachers in Hubei Province, China. These teachers are grappling with declining satisfaction and increasing job burnout. To address this, the present study conducted a comprehensive questionnaire survey, collecting data from 502 teachers across 36 universities, followed by structural equation modeling to analyze the influencing factors. Results indicate a significant negative impact of job burnout on job satisfaction (path coefficient = -0.173, p < 0.014), contrasted by positive contributions from social support (0.247, p < 0.001), self-efficacy (0.221, p < 0.001), and professional identity (0.167, p < 0.001). Mediation analysis further reveals that these resources collectively mitigate burnout’s effect (total indirect effect = -0.324, p < 0.01), aligning with demand-resource perspectives. The findings, reflecting low job satisfaction (mean = 2.39) and high emotional exhaustion (mean = 3.63), highlight the need for targeted interventions to address Hubei’s unique educational pressures, such as workload strain and resource disparities.